1998
DOI: 10.1073/pnas.95.4.1752
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antigenemia on the bioactivity of infused anti-Tac antibody: Implications for dose selection in antibody immunotherapies

Abstract: In patients with malignancies and immune disorders expressing Tac (␣ chain of the interleukin 2 receptor; CD25), physiologic shedding of this receptor may lead to high blood levels of the soluble form (sTac). This system was used to model the interaction of soluble antigen with antibody in therapeutic settings and to develop rational principles to optimize the delivery of antibody to tumor target cells. First, we confirmed that sTac in vivo can block anti-Tac binding sites and diminish antibody binding to Tac؉… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…The model presented here is consistent with this data and indicates that the RIT-mesothelin complex in tumor ECS is this reservoir. The model is also consistent with the report of Junghans et al(9) that the shed antigen-antibody complex can supply the antibody to bind leukemic cells and solid tumors when free antibody is depleted.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The model presented here is consistent with this data and indicates that the RIT-mesothelin complex in tumor ECS is this reservoir. The model is also consistent with the report of Junghans et al(9) that the shed antigen-antibody complex can supply the antibody to bind leukemic cells and solid tumors when free antibody is depleted.…”
Section: Discussionsupporting
confidence: 92%
“…Such shedding can be expected to significantly influence the delivery of anti-cancer agents that use these antigens as the delivery target(9). However, no theoretical study has been reported on the effect of antigen shedding on the delivery of these agents in solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In a third example, researchers treated patients with an anti-CD25 antibody (anti-Tac antibody) and studied the amount of circulating antibody that was available for binding ex vivo to target cells. In one patient, because of shed antigen, initially only a fraction of the infused antibody bound ex vivo to target cells; however, after the infusion of a total dose of ∼ 30 mg, the ex vivo activity reached a plateau at its maximal theoretical level [36]. This suggests that pretreatment with naked antibody to neutralise the shed antigen may lead to an increase in delivery to tumours and, ultimately, in the antitumour activity of the subsequently administered immunoconjugate.…”
Section: Clearance As Antibody-drug Conjugatementioning
confidence: 89%
“…Previously we published [18, 19] analyses of the impact of soluble TAC (IL-2R alpha) on the bindability of administered anti-IL-2R alpha and on the impact of tumor burden on antibody dosing. There we indicated that in situations such as with high specific activity radiolabeled antibody one must use the soluble circulating IL-2R alpha levels to provide the optimized dose of unlabeled dacliuzumab.…”
Section: [2] Methodsmentioning
confidence: 99%